Measuring Calves' Usage of Multiple Environmental Enrichment Objects Provided Simultaneously - Strappini, Ana C.; Monti, Gustavo; Sepúlveda-Varas, Pilar; de Freslon, Inès; Peralta, José M. (Frontiers in Veterinary Science, 2021)
This study aims to assess calf usage of five potential enrichment devices provided simultaneously. We used 25 weaned Holstein-Friesian calves housed in groups of five (five replicates), and their behaviour was recorded continuously with video cameras. This longitudinal observational study used a pen equipped with a mechanical and fixed brush, cowhide, horizontal and vertical ropes. Data collected included how many visits each object received per day, the type of objects usage, and the duration of the visits. Calves used all five objects at least once, and they used items more during the daytime than at night. Brushes were used mainly for grooming (e.g., rubbing or scratching), while ropes and cowhide for oral interactions (e.g., licking, chewing, and biting), most likely to lack oral stimulations that would naturally be satisfied by suckling and grazing at this age. The objects most frequently used were the mechanical brush and the horizontal rope, and they received the highest number of visits (214.9 bouts/day and 154.9 bouts/day, respectively). The least chosen object was the stationary brush, which had the lowest number of visits (62.9 bouts/day). The provision of multiple enrichment objects for weaned calves should be considered as they may add complexity and novelty to barren environments.